Effect of lifestyle modifications on anthropometric, clinical, and biochemical parameters in adolescent girls with polycystic ovary syndrome: a systematic review and meta-analysis - Abdolahian, Somayeh (BMC Endocr Disord, 2020)
BACKGROUND: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of childbearing age. This study aimed to compare the effects of lifestyle interventions on anthropometric, clinical, and biochemical parameters in adolescent girls with PCOS. METHODS: PubMed, Scopus, and Web of Science was systematically searched to retrieve studies investigating the effects of lifestyle modifications in adolescent girls with PCOS, which were published up to December 2019. The primary outcome was Body Mass Index (BMI) and secondary outcomes were all manifestations of PCOS, including clinical, metabolic, and hormonal parameters. Random effect meta-analysis was applied for significant results. Publication bias was assessed using the Egger test. RESULTS: This study showed significant improvements in luteinizing hormone (LH) (Pooled SMD = − 0.1.23; 95% CI, − 2.44 to − 0.03), and Free Androgen Index (FAI) levels (Pooled SMD = − 0.78 95% CI, − 0.1.42 to − 0.13) in adolescent girls receiving lifestyle intervention compared to baseline. This study also revealed that diet modifications alone were associated with a significant decrease in Body Mass Index (BMI) (Pooled SMD = − 0.45; 95% CI, − 0.76 to − 0.13), and FG score (Pooled SMD = − 0.81; 95% CI, − 1.33 to − 0.28). Exercise interventions were associated with significant changes in the menstrual cycles (Pooled SMD = 1.16; 95% CI, 0.72 to 1.61), Ferriman-Gallwey (FG) score (Pooled SMD = − 0.57; 95% CI, − 0.99 to − 0.15), LH (Pooled SMD = − 056; 95% CI, − 0.98 to − 0.14), Anti-Müllerian Hormone (AMH) (Pooled SMD = − 0.81; 95% CI, − 0.1.24 to − 0.38), and Triglyceride (TG) levels (Pooled SMD = − 0.32; 95% CI, − 0.62 to − 0.02). CONCLUSION: This meta-analysis concluded lifestyle interventions, such as diet and exercise, can improve some clinical, metabolic, and hormonal parameters in adolescent girls with PCOS.